Effect of three different cultivars of Lepidium meyenii (Maca) on learning and depression in ovariectomized mice - Gonzales Gustavo F; Gasco Manuel; Dávila Sonia; Caldas Maria; Rubio Julio (BMC, 2006)
Abstract Background Lepidium meyenii Walp. (Brassicaceae), known as Maca, is a Peruvian hypocotyl growing exclusively between 4000 and 4500 m altitude in the central Peruvian Andes, particularly in Junin plateau and is used traditionally to enhance fertility. Maca is a cultivated plant and different cultivars are described according to the color of the hypocotyls. Methods The study aimed to elucidate the effect of Yellow, Red and Black Maca on cognitive function and depression in ovariectomized (OVX) mice. In all experiments OVX mice were treated during 21 days and divided in four groups: control group, Yellow Maca, Red Maca and Black Maca. Latent learning was assessed using the water finding task and the antidepressant activity of the three varieties of Maca was evaluated using the forced swimming test. Animals were sacrificed at the end of each treatment and the uterus were excised and weighed. Results Black Maca was the variety that showed the best response in the water finding task, particularly in the trained mice. The three varieties were effective to reduce finding latency in non trained and trained mice (P < 0.05). In the force swimming test, all varieties assessed reduced the time of immobility and increased uterine weight in OVX mice. Conclusion Black Maca appeared to have more beneficial effects on latent learning in OVX mice; meanwhile, all varieties of Maca showed antidepressant activity.